The role of indirect learning activities in the classroom: El papel de las actividades de aprendizaje indirecto en el aula (2024)
Introduction: For the language learning process, it is essential to have a relaxed and positive classroom environment, as this indirectly contributes to learning by facilitating students’ readiness to use the language. Methodology: In this context, the present research explored the most frequently used indirect learning activities by teachers in their practice. The study design is qualitative and exploratory. A semi-structured interview with 13 predefined questions and the flexibility to include follow-up questions was used to explore the participants’ perspectives and experiences. Data were collected on the frequency of use of learning activities and the reasons for their inclusion in the classroom, from a total of 13 teachers belonging to a language center in northern Mexico. The data were analyzed using content analysis. Results and Discussion: The results revealed that teachers show a notable concern for creating a good classroom environment through activities in the form of games or competitions. Conclusions: it is observed that indirect learning activities are consistently included as a basis for the incorporation of other activities, which emphasizes the importance of carefully selecting activities in the educational process, considering both the direct and indirect learning objectives.